(untitled) (PANGEEA, 2025)
Few thousands years ago in Rosia Montana there were drilled the depths, looking for the golden ores. These precious ores, once they were brought to the surface they were broken into pieces, to obtain the metal. In The Ancient Time the people used to break into pieces the golden rocks water. First they used them in rudimentary equipments, then in poles with a lot of arrows, which gave a big productivity. When Transylvania went over Austrian administration big changes were produced for those who work with gold, especially for their activity and life. To have more time, the water for poles, there were made big puddles which stored water and left it free when they needed it. It was exploited all the potential of the local relief. Today you can see over 105 puddles or locks, which are situated in the north of the village, at Zănoaga, Gârda and Rotundu, in the east of the village at Vârşi, Curmătura, Poieni, Sulley and Ghergheleu and more in the south at Cetate, Cârnic, Carpeni and Tille. They can be recognized after the reed and eventually after the prominent field, which showed us the place where a puddle was. The biggest puddles, filled with water, can be seen in the beautiful landscape. Unfortunately, they were not established in the tourists’ lines for this part of Abrud, and that’s why they remained old historic relics which reminded us of the prosperous mining. The biggest and most important puddles are: Tăul cel Mare, Tăul Ţarinei, Tăul Cornii, Tăul Brazi, Tăul Anghel, Tăul Seliştii, Tăul Cartuş and Tăul Ţapului. They are very precious for the tourists and it is necessary simple arrangements and some signs for you to see the paths, so that they bring more and more tourists. It would be necessary a whole day of travelling through this beautiful landscape. Key words: golden ores, equipments, puddles, historic relics , landscape, tourism.